2007
DOI: 10.2223/jped.1594
|View full text |Cite
|
Sign up to set email alerts
|

Brain death: medical management in seven Brazilian pediatric intensive care units

Abstract: NEEP-Br) 9Resumo Objetivo: Avaliar a incidência de morte encefálica (ME), bem como as condutas e protocolos adotados após confirmação diagnóstica em sete unidades de tratamento intensivo pediátrico (UTIP) localizadas em três regiões brasileiras. Métodos:Estudo transversal e multicêntrico baseado na revisão e análise retrospectiva de prontuários de todos os óbitos ocorridos entre janeiro de 2003 e dezembro de 2004 em sete UTIP localizadas em Porto Alegre (duas), São Paulo (duas) e Salvador (três). Dois resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 13 publications
1
13
2
12
Order By: Relevance
“…6 It is worth noting that, in this study, 30% of cases of clinical BD (44 out of 147) were not certified using ancillary methods, which harbors the potential for lost donors, which is higher than what has been reported by a multicenter study conducted in Brazil, 13 which showed that 20% of BD cases were not certified. It has been considered that the implications of adopting a health policy in relation to mandatory ancillary methods are subjected to ethical and cultural conditions inherent to each country and are worth discussing in the scientific society as a whole.…”
contrasting
confidence: 60%
“…6 It is worth noting that, in this study, 30% of cases of clinical BD (44 out of 147) were not certified using ancillary methods, which harbors the potential for lost donors, which is higher than what has been reported by a multicenter study conducted in Brazil, 13 which showed that 20% of BD cases were not certified. It has been considered that the implications of adopting a health policy in relation to mandatory ancillary methods are subjected to ethical and cultural conditions inherent to each country and are worth discussing in the scientific society as a whole.…”
contrasting
confidence: 60%
“…The median duration of hospitalisation was 12 days (IQR: [9][10][11][12][13][14][15][16][17] pitalisation and the start of BD evaluation was seven days (IQR:5-10.5), and the median duration of brain death evaluation was three days (IQR:2-7). In the current study, we first confirmed BD in patients by clinical criteria then performed a confirmatory ancillary test.…”
Section: Resultsmentioning
confidence: 99%
“…Different pediatric studies have found different rates between 11.6% and 37% [11][12][13]. These differences may be due to the type of ICU, e.g., trauma referral centres, local practice differences such as the emphasis on organ donation, comfort with the determination of BD, the year of study, and patient demographics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on various philosophical principles, these parameters stipulate variable intervals between clinical trials, various assignments of the professionals in charge of carrying out such tests and whether or not the execution of additional procedures are necessary 5 . A certain uneasiness is still frequent among the professionals involved, especially among critical care physicians, at the time of suspension of life support or at the time of filling in the death certificate 6,7 .…”
Section: Brain Death: a Finished Discussion?mentioning
confidence: 99%